Sustainability in reference and response to COVID-19 pandemic - Maulan, Suhardi (Universiti Putra Malaysia Press, 2020)
This year we are been surprised by the spread of novel coronavirus name COVID-19. Due to the virus’s active infectious nature, the virus that had started in Wuhan, China has now spread all over the world. World Health Organization or WHO declares that COVID -19 is a pandemic and to date, almost 9.6 million people have been infected and almost 500,000 people have perished. Almost no countries have been spared and the calamity has been equated with Spanish Flu Pandemic from 1918 – 1920. With COVID-19 spread rapidly, many countries had issued a lockdown order in which force people to stay indoors, practice social distancing, and maintain a high level of personal hygiene. The situation has caused businesses and economies to stand still and many countries started to look at the short- and long-term measures to reignite the economy, reduce economic retraction, and to avoid recession. In contrast, during the lockdown, the nature and wellbeing of the environment thrive. Our rivers are getting cleaner so does the air quality due to reduce numbers of factory operated and vehicles on the roads. The situation shows the two-prong effects if people’s activities are reduced at the extreme. Nevertheless, as countries slowly lifting the lockdown measures and people return to normalcy, it is very important to observe and be creative on how to ensure that both nature and economic activities can thrive sustainably.